Temporal Patterns of Energy Intake in Relation to Cognitive Function and Its Decline: A Community-Based Cohort Study in China. (14th June 2022) - Tao, Yang; Chen, Hui; Tao, Yang; Li, Min-Dian; Gu, Yuxuan; Yu, Dongmei; Yuan, Changzheng
Abstract: Objectives: Temporal pattern of energy intake (TPEI) has been related to multiple cardiometabolic diseases and mortality. However, its association with cognitive function remains poorly understood. We aimed to assess the prospective association of the TPEI with cognitive function and its decline in a community-based cohort study in China. Methods: The study included data from 3342 participants aged over 55 years old from the China Health and Nutrition Study (CHNS). Dietary data were collected using 3-day 24-hour dietary recalls at study baseline in 1997 and every 2–4 years thereafter. TPEI was identified using the k-means algorithm. Cognitive function was assessed up to four times using the Telephone Interview for Cognitive Status-modified (TICS-m) from 1997–2006. Linear mixed models were used to estimate the association of TPEI with the level of cognitive function and its decline in subsequent years. Results: We identified six TPEIs: breakfast-dominant, lunch-dominant, dinner-dominant, evenly-distributed, breakfast-skipping, and snack-rich patterns. Compared with the evenly-distributed temporal pattern, other patterns were all related to lower cognitive function scores, with differences being −0.94 (95%CI: −1.37, −0.51, points) for breakfast-dominant pattern, −1.18 (95%CI: −1.67, −0.69, points) for lunch-dominant pattern, −0.97 (95%CI: −1.43, −0.51, points) for dinner-dominant pattern, −1.05 (95%CI: −1.70, −0.40, points) for snack-rich pattern, and −1.32 (95%CI: −1.66, −0.99, points) for breakfast-skipping pattern ( P  < 0.05). Particularly, the breakfast-skipping pattern was also associated with a significantly faster cognitive decline (−0.40 [−0.48, −0.32] point/year) compared with the slowest cognitive decline (−0.26 [−0.31, −0.21] point/year) in the evenly-distributed pattern. Conclusions: Maintaining an evenly-distributed temporal pattern of energy intake was associated with better cognitive function and slower cognitive decline in later life, underscoring the importance of managing and balancing energy intake across major meals throughout the day. Funding Sources: This work was supported by the Zhejiang University Education Foundation Global Partnership Fund (granted to CY).